Delineating effects of angiopoietin-2 inhibition on vascular permeability and inflammation in models of retinal neovascularization and ischemia/reperfusion - Canonica, Jérémie; Foxton, Richard; Garrido, Marina Garcia; Lin, Cheng-Mao; Uhles, Sabine; Shanmugam, Sumathi; Antonetti, David A.; Abcouwer, Steven F.; Westenskow, Peter D. (Frontiers in Cellular Neuroscience, 2023)
Clinical trials demonstrated that co-targeting angiopoietin-2 (Ang-2) and vascular endothelial growth factor (VEGF-A) with faricimab controls anatomic outcomes and maintains vision improvements, with strong durability, through 2 years in patients with neovascular age-related macular degeneration and diabetic macular edema. The mechanism(s) underlying these findings is incompletely understood and the specific role that Ang-2 inhibition plays requires further investigation. We examined the effects of single and dual Ang-2/VEGF-A inhibition in diseased vasculatures of JR5558 mice with spontaneous choroidal neovascularization (CNV) and in mice with retinal ischemia/reperfusion (I/R) injuries. In JR5558 mice, Ang-2, VEGF-A, and dual Ang-2/VEGF-A inhibition reduced CNV area after 1 week; only dual Ang-2/VEGF-A inhibition decreased neovascular leakage. Only Ang-2 and dual Ang-2/VEGF-A inhibition maintained reductions after 5 weeks. Dual Ang-2/VEGF A inhibition reduced macrophage/microglia accumulation around lesions after 1 week. Both Ang-2 and dual Ang-2/VEGF-A inhibition reduced macrophage/microglia accumulation around lesions after 5 weeks. In the retinal I/R injury model, dual Ang-2/VEGF-A inhibition was statistically significantly more effective than Ang-2 or VEGF-A inhibition alone in preventing retinal vascular leakage and neurodegeneration. These data highlight the role of Ang-2 in dual Ang-2/VEGF-A inhibition and indicate that dual inhibition has complementary anti-inflammatory and neuroprotective effects, suggesting a mechanism for the durability and efficacy of faricimab in clinical trials.